2002
DOI: 10.1095/biolreprod.101.001446
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Testis-Specific Member of the Phosphatidylethanolamine Binding Protein Family, pebp-21

Abstract: The phosphatidylethanolamine binding proteins (pebps) are an evolutionarily conserved family of proteins recently implicated in mitogen-activated protein (MAP) kinase pathway regulation, where they are called raf kinase inhibitory proteins. Here, we describe the cloning, cellular localization, and partial characterization of a new member, pebp-2, with potential roles in male fertility. Expression data show that pebp-2 is a testis-specific 21-kDa protein found within late meiotic and haploid germ cells in a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 53 publications
3
54
0
Order By: Relevance
“…According to O'Bryan and colleagues (10), previously identified PEBPs can be grouped into three subfamilies; the majority of differences between these subfamilies are in the N-terminal residues (those preceding the PE-binding domain), especially the first 10 amino acids. Members of the three subfamilies share similar overall features, including length (each being ϳ190 residues) and amino acid composition in functional domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to O'Bryan and colleagues (10), previously identified PEBPs can be grouped into three subfamilies; the majority of differences between these subfamilies are in the N-terminal residues (those preceding the PE-binding domain), especially the first 10 amino acids. Members of the three subfamilies share similar overall features, including length (each being ϳ190 residues) and amino acid composition in functional domains.…”
Section: Discussionmentioning
confidence: 99%
“…Mapping of the binding domains has shown that MEK and Raf-1 bind to overlapping sites in hPEBP1, whereas MEK and hPEBP1 associate with different domains in Raf-1, and Raf-1 and hPEBP1 bind to different sites in MEK. In addition, mPEBP2, a recently characterized novel testis-specific member of the phosphatidylethanolamine-binding protein family, colocalizes with members of the mitogen-activated protein kinase pathway in late spermatocytes and spermatids and on the midpiece of epididymalsperm (10).…”
mentioning
confidence: 99%
“…54 Its expression is particularly high in liver and testis; 55 the latter representing a tissue-specific isoform. 56 In the brain, an N-terminal fragment of PEBP known as the "hippocampal cholinergic neurostimulating peptide" (HCNP) seems to serve as a transmitter and an endocrine factor. 57 PEBP is primarily a cytosolic protein, but is able to bind to cellular and model membranes through its N-and C-terminal ends.…”
Section: Table 1 Autophagosomally Enriched Membrane-associated Proteinsmentioning
confidence: 99%
“…During the process of cloning components of the mouse sperm tail, as described previously (Hickox et al, 2002;O'Bryan et al, 1998), a partial fragment of suc1-associated neurotrophic factor target 2 (Snt-2) was identified. The missing 3Ј end was cloned using 3Ј rapid amplification of cDNA ends (RACE), utilizing the FirstChoice TM RLM-RACE kit (Ambion, Texas) as previously described (O'Bryan et al, 2000b;Troutt et al, 1992), using the primers F1701A 5Ј-AGC-CCAATGCACCTATGAG-3Ј, F1701B 5Ј-CTTCCTCCTGTGTGGGAGAG-3Ј and the supplied adaptor primer, AP3Ј.…”
Section: The Identification Of Fgfr Signaling Components In Sperm Devmentioning
confidence: 99%